Puzzle Activities Enhances Fine Motor Skill Development in Preschool-Aged Children - Romandita, Shalna Faizza; Barlianto, Wisnu; Ulfah, Mega (Women, Midwives and Midwifery, 2026)
Background: rapid physical and psychological growth, especially fine motor development, characterizes the preschool period. Delays in fine motor skills can affect children's self-confidence and learning in the future. Purpose: this study aimed to examine the effect of puzzle-based educational stimulation on fine motor outcomes among preschool children using the Denver Developmental Screening Test II (DDST II). Methods: a quasi-experimental pretest–posttest control group design was employed, involving 46 children from TK Dharma Wanita 1 Keniten, Kediri, divided equally into intervention and control groups. Fine motor outcomes were assessed based on DDST II fine motor adaptive items, including tasks such as building towers, copying shapes, and drawing. Results: the fine motor development status of preschool aged children in the intervention group increased from 60.9% at pretest to 100% at posttest, whereas the control group also showed a smaller improvement from 78.3% to 95.7%. The Wilcoxon test indicated a significant improvement within the intervention group (p < 0.005). However, the Mann Whitney U test showed no significant difference between the intervention and control groups in the posttest scores Conclusion: puzzle-based stimulation effectively enhances children’s fine motor development, highlighting its potential as an engaging educational strategy in early childhood programs